Small, mobile, persistent: Trifluoroacetate in the water cycle – Overlooked sources, pathways, and consequences for drinking water supply. (1st December 2017) - Scheurer, Marco; Nödler, Karsten; Freeling, Finnian; Janda, Joachim; Happel, Oliver; Riegel, Marcel; Müller, Uwe; Storck, Florian Rüdiger; Fleig, Michael; Lange, Frank Thomas; Brunsch, Andrea; Brauch, Heinz-Jürgen
Abstract: Elevated concentrations of trifluoroacetate (TFA) of more than 100 μg/L in a major German river led to the occurrence of more than 20 μg/L TFA in bank filtration based tap waters. Several spatially resolved monitoring programs were conducted and discharges from an industrial company were identified as the point source of TFA contamination. Treatment options for TFA removal were investigated at full-scale waterworks and in laboratory batch tests. Commonly applied techniques like ozonation or granulated activated carbon filtration are inappropriate for TFA removal, whereas TFA was partly removed by ion exchange and completely retained by reverse osmosis. Further investigations identified wastewater treatment plants (WWTPs) as additional TFA dischargers into the aquatic environment. TFA was neither removed by biological wastewater treatment, nor by a retention soil filter used for the treatment of combined sewer overflows. WWTP influents can even bear a TFA formation potential, when appropriate CF3 -containing precursors are present. Biological degradation and ozonation batch experiments with chemicals of different classes (flurtamone, fluopyram, tembotrione, flufenacet, fluoxetine, sitagliptine and 4:2 fluorotelomer sulfonate) proved that there are yet overlooked sources and pathways of TFA, which need to be addressed in the future. Graphical abstract: Image 1 Highlights: TFA is almost ubiquitary occurring in surface water. TFA removal from raw waters used for drinking water production is difficult. Only ion exchange or reverse osmosis can be successfully applied in waterworks. TFA discharge is not limited to photochemical degradation of precursors in the atmosphere. TFA is not degraded in WWTPs. Degradation of precursors can result in higher effluent concentrations.